Multiple Sclerosis in Children: Current and Emerging Concepts - Brenton, J. Nicholas; Kammeyer, Ryan; Gluck, Lauren; Schreiner, Teri; Makhani, Naila (Seminars in Neurology, 2020)
Multiple sclerosis is being increasingly recognized and diagnosed in children. In the past several years, advances have been made in diagnosing multiple sclerosis in children, identifying new genetic and environmental risk factors, delineating underlying immunobiology, characterizing imaging findings, and implementing new treatment strategies. In this review, we discuss these advances. Future research into the determinants of multiple sclerosis in children and into new treatment options will be aided by continued international collaboration.
Keywords: multiple sclerosis; children; pediatric